Comparative Study for Application of Polypropylene Monofilament Light Mesh, Polypropylene Monofilament Heavy Mesh and Self Gripping Polypropylene Mesh in Patients with Inguinal Hernia Surgically Treated with Lichtenstein Technique - Bozinovks Beaka, Gordana; Prgova Veljanovska, Biljana; Zdravkovska, Milka; Kalamaras, Patricija (Lietuvos chirurgija, 2020)
Background / Objective. In our clinical study we have compared the results of intraoperative and postoperative period in patients with inguinal hernia treated operatively with Lichtenstein technique, where one of three different polypropylene meshes has been applied: polypropylene monofilament light mesh, polypropylene monofilament heavy mesh and self gripping polypropylene mesh. Follow up period have been one year. Methods. This study represents randomized, retrospective-prospective, comparative clinical study where 243 patients have been divided into three groups depends of prosthetic mesh that was applied with Lichtenstein technique. We have evaluated the connection between types of used mesh with some of followed parameters: postoperative pain intensity, postoperative patient mobilization, postoperative surgical site occurrences, duration of hospitalization, chronic pain, filling of foreign body in inguinal area and development of recurrences. Results. Patients with applied self gripping polypropylene mesh have significantly lowest pain, lowest hospital stay and lowest duration of surgical procedure than other two groups of patients. In term of chronic pain, only statistically significance we confirmed between the groups of heavy monofilament mesh and self griping polypropylene mesh, where higher number of patients from group with monofilament polypropylene light mesh reported chronic pain. In our study we confirmed that working status and patient age have significant influence on the intensity of postoperative pain in all three patients group. There is no statistical correlation between type of the mesh and surgical site occurrence rate. Conclusion. Patients with applied self gripping polypropylene mesh have significantly lowest pain, lowest hospital stay, lowest duration of surgical procedure and less number of patients experienced feeling of “foreign body” in their groin than other two groups of patients.
Keywords: inguinal hernia; Lichtenstein technique; polypropylene meshes; self gripping mesh